The Influence of Workload, Burnout, Distress on Nurses' Performance Post Covid-19 Pandemic - Sukma Hapsari; Jenny Marlindawani Purba; Taufik Ashar (Indonesian Journal of Global Health Research, 2024)
Workload, burnout and distress are closely related to nurse performance, because increasing workload, burnout and distress can reduce nurse performance. The purpose of this study was to determine the effect of workload, burn out, distress on the performance of nurses after the Covid-19 pandemic. Method: This study is quantitative with a causal associative design. The population in this study were nurses at the Prof. Dr. M. Ildrem, Metal Hospital, totaling 184 people, with a sample of 65 people in the study. Data were collected using questionnaire. Data were analyzed using multiple linear regression. The study shows that workload and distress influence the performance of nurses after the Covid-19 pandemic at the Prof. Dr. M. Ildrem, Mental Hospital, Medan, while burn out has no effect on the performance of nurses after the Covid-19 pandemic at the Prof. Dr. M. Ildrem, Mental Hospotal, Medan. Workload, burn out and distress together influence the performance of nurses after the Covid-19 pandemic at the Prof. Dr. M. Ildrem, Mental Hospital, Medan. Hospitals need to pay attention to workload elements that can affect nurses' performance, as well as exploring the individual abilities of nurses, providing opportunities for nurses to be creative and self-actualizing to reduce burn out as well as screening nurses for psychological problems regularly to support nurses who work in the Mental Hospital.